Pengaruh Kekerasan Agregat Kasar Quarry Laha Dan Quarry Passo Terhadap Mutu Beton Rencana - Latuapo, Aji Samad; Soumokil, Musper David; Tuanakotta, Abraham (JURNAL ILMIAH NUSANTARA, 2025)
The quality of concrete is influenced by the quality of the aggregate and the properties of the aggregate will vary according to geological, geographical and climatic conditions. Material from Quarry Laha and Quarry Passo is often used as construction material for concrete and other infrastructure in the city of Ambon and its surroundings. As a location where this material is frequently used, the quality of this material needs to be tested before being used as a base material for mixing concrete so that it meets the specifications determined for construction and infrastructure development.The purpose of this case study is to determine the hardness value of Quarry Laha and Quarry Passo coarse aggregates on the quality of K-250 concrete and to know and understand the physical and mechanical properties of coarse aggregates and their influence on the quality of K-250 concrete.In this research, the test used six test objects, namely three test objects for Quarry Laha and three test objects for Quarry Passo, the mixture ratio used for Quarry Laha was 1 : 1.4 : 2.7 : 0.5 while Quarry Paaso was 1 : 1.3 : 2.4 : 0.6 with an abrasion value for Quarry Laha of 18% and Quarry Passo of 26%, and the average compressive strength value of concrete for Quarry Laha was 24.68 Mpa and Quarry Passo of 24.10 Mpa. These results show that hard aggregate produces high compressive strength of concrete and vice versa.